Comparative histological changes in the structure of the spleen and kidneys of experimental chickens exposed to the action of “Guidamis” as an adjuvant for vaccination against infectious bronchitis - Asrutdinova Rezilya (BIO Web of Conferences, 2020)
The article provides a histological description of the internal organs – the spleen and kidneys of chickens exposed to the action of “Guidamis” as an adjuvant. A lysate was tested as part of a sample of the vaccine PB-07 against infectious bronchitis developed by researchers of the Department of Virology and Tumor Diseases of Birds of the Russian Agricultural Academy (Lomonosov). The experiments were carried out on Lohmann Brown chickens in the conditions of the Laishev branch of “Ak Bars” Poultry Company, the Republic of Tatarstan. The prolonged action of the vaccine against infectious bronchitis and the use of “Guidamis” as an adjuvant was manifested as an increase in the proliferation and differentiation of lymphoid tissues in the numerous lymph nodes. The use of the vaccine and the adjuvant had a weak reactogenic effect. In the spleen of control chickens, hyperplasia of lymphoid tissue cells is weakly expressed. In the periarterial zone of nodules of the thymus-dependent lymphocytes, the cell density is low. In the kidneys, for fourteen days after the vaccination against infectious bronchitis using Guidamis, the moderate granular dystrophy of the epithelium, mainly of individual distal tubules, and local moderate manifestations of edema of the capsule of the renal corpuscles were observed. In the kidneys, signs of pronounced edema of the capsule cavity, significant disturbances in the patency of the tubular network caused by swelling and partial desquamation of the epithelium, as well as the presence of epithelium and protein mass in the lumen of the tubules, were observed.